Synthesis of 3 alkyl and 1,3-Bis(alkyl)indolizine amides from a-bromohydroxamates - Mane, Kishor D.; Bagwe, Sagar S.; More, Satish G.; Suryavanshi, Gurunath (Tetrahedron Letters, 2023)
A simple and catalyst-free method has been developed for the synthesis of hindered indolizine amide derivatives from functionalized alkyl bromides. The reaction of a variety of indolizine derivatives with azaoxyallyl cations generated in situ from a-bromoamides afforded a wide range of synthetically important mono- and di-alkylated indolizine amide derivatives in good to excellent yields.@2023 Elsevier Ltd. All rights reserved.
Keywords: a -Bromohydroxamates; Amides; HFIP; Indolizine